2008
DOI: 10.4161/oxim.1.1.6958
|View full text |Cite
|
Sign up to set email alerts
|

Sesamin Modulates Tyrosine Hydroxylase, Superoxide Dismutase, Catalase, Inducible No Synthase and Interleukin‐6 Expression in Dopaminergic Cells Under Mpp+‐Induced Oxidative Stress

Abstract: Oxidative stress is regarded as a mediator of nerve cell death in several neurodegenerative disorders, such as Parkinson's disease. Sesamin, a lignan mainly found in sesame oil, is currently under study for its anti-oxidative and possible neuroprotective properties. We used 1-methyl-4-phenyl-pyridine (MPP+) ion, the active metabolite of the potent parkinsonism-causing toxin 1-methyl-4-phenyl-1,2,5,6-tetrahydropyridine, to produce oxidative stress and neurodegeneration in neuronal PC12 cells, which express dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 79 publications
4
39
0
Order By: Relevance
“…Our results indicate that SO restored the MnSOD protein expression in lesion?SO group and the elevated MnSOD level as compared with lesion demonstrates that SO enhances the ability of SOD to eliminate superoxide radicals formed during 6-OHDA induced oxidative stress. Lahaie-Collins et al [16] reported similar finding that sesamin modulates superoxide dismutase and catalase in dopaminergic cells under 1-methyl-4-phenylpyridinium (MPP? )-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Our results indicate that SO restored the MnSOD protein expression in lesion?SO group and the elevated MnSOD level as compared with lesion demonstrates that SO enhances the ability of SOD to eliminate superoxide radicals formed during 6-OHDA induced oxidative stress. Lahaie-Collins et al [16] reported similar finding that sesamin modulates superoxide dismutase and catalase in dopaminergic cells under 1-methyl-4-phenylpyridinium (MPP? )-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 63%
“…SO in comparison to other dietary oils such as groundnut, canola and sunflower oil depicted better protection against increased blood pressure, hyperlipidemea and LPO by increasing enzymatic and non-enzymatic antioxidants [14]. Sesamin, sesamolin and tocopherols are powerful antioxidants in SO, and have been reported to possess a broad spectrum of pharmacological effects including neuroprotective, anti-inflammatory, antihypertensive and antimutagenic [15][16][17]. Sesamin and sesamolin have been shown inhibitory effect on LPS-activated p38 mitogen activated protein kinase (MAPK) and nuclear factor kB (NF-kB) activation in microglial cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MPP + induces marked increases in IL-6, IL-1b and TNF-a mRNA levels and protein concentrations in N9 microglial cells (Bournival et al, 2012;Lahaie-Collins et al, 2008), suggesting a direct activation of microglia by MPP + . Here we provide further evidence showing that MPP + can directly induce microglial inflammatory response.…”
Section: Discussionmentioning
confidence: 96%
“…Salvianic acid A and salvianolic acid B from Salvia miltiorrhiza have been shown to be effective on 6-OHDA or MPP + toxicity in vitro Tian et al, 2008). Sesamin from Sesamum indicum or Acanthopanax senticosus has reported to antagonize MPP + toxicity in vitro (Lahaie-Collins et al, 2008) and prevented loss of DA cells, bradykinesia and depression in rotenone model (Fujikawa et al, 2005a).…”
Section: Phenylpropanoids and Lignansmentioning
confidence: 97%